A Loyalty Program in the Area of Digital Transformation Based on the Example of the Costa Coffee Brand - Gwiaździński, Emilian; Wadlewski, Aron-Axel (The Best Practice of Marketing Management in Polish and International Enterprises: The Marriage of Science and Business – Case Studies, 2022)
The widespread digital transformation resulting from the influence of three megatrends - globalization, dynamic development of technology and the new consumer on the market, has forced companies to adapt to new market conditions. The consumer, who is the last link in the chain, focusing only on consumption, is now the co-creator of the market offer. He is more sensitive to marketing messages using modern tools such as mobile devices, among others. This study presents the process of adaptation of the Costa Coffee brand to the new market environment on the example of its loyalty program.